Habitatul rural în comitatul Arad în secolul al XVIII-lea - Ghita, Eugen (2010)
Abstract: The present study aims to investigate in terms of quantitative and qualitative perspectives the rural habitat in the county of Arad during the eighteenth century. The dynamics of settlements, their evolution over the century, changes occurred in the types of environments were conducted in conjunction with the policy of the new imperial authorities and in accordance with the populationist policy of the Habsburg Empire. The rural habitat which predominated in the Arad County suffered changes of great importance not only just as a consequence of the official systematization policy, but also as a result of the constant demographical increase which occurred in the eighteenth century